The Challenges to the Bulgarian “Green Transition” - Самандов, Георги (Научни трудове, 2025)
The European citizen wants a better life for themselves and the planet. Our target is to keep the air we breathe, the food we eat, the resource we use, clean and safe.The “green wave” has covered Europe and the rest of the civilized world. The proof of that are the elections in 2019 and the new course of Europe with so-called "Green Deal". The goal of the European green politics is to respond to the growing challenges of current post-industrial socio-economic model, which comes entirely at the expense of our planet and its resources. There is no going back and no one will wait for the Bulgarian energy transition. We must build ambition plan for many difficult and unpopular changes – strategic, technical and mental. The main target should be the usage of the local resources and their combining with the needs of the industry and the citizens. For more than decade the Bulgarian did not use the experience of our European partners. The time of the green economy has come and we must use this chance for a better life.The document identifies the problematic units in the current Bulgarian energy model and provides potential solutions to make the much-needed green transition.